A quality feed trust model for data transactions at cloud - Kaur, Usvir; Mahajan, Manish; Singh, Dheerendra (International Journal of Engineering and Technology, 2018)
The cloud is one of the most emerging platforms of the modern world. Although the complete cloud model is going to take a while to act practically the research industry has started focusing on the data storage and futuristic transaction problems.This paper focuses on developing a trust model based on the user authentication and feedbacks.The proposed work combines the authentication structures with a job scheduling models which looks into the partition of the job. The proposed model utilized a feedback solution model to maintain the trust model of the cloud executioner. The evaluation of the proposed work is done on the base of Quality of Service (QoS) parameters. The evaluated parameters are also compared with previous QOS trust model.Â